Implementasi Sistem Layanan Dukungan dan Pengaduan Pelanggan pada Produk Justmine Beauty Berbasis Mobile - Hidayah, Septia Rizka; Sejati, Rr. Hajar Puji (Teknik Informatika Universitas Pamulang, 2023)
Justmine Beauty is a series of daily skin care products that can overcome all skin types, natural ingredients taken from water can provide nutrition and nourish facial skin, then specially formulated and dermatologically tested which has halal certification and BPOM so that it is suitable for skin problems and accompany activities, keep facial skin healty with Justmine Beauty. Generally, customers conduct consultations only using WhatsApp or other social media where later this consultation history is also lost because it is not saved. Customer complaints contained in the brans mostly contain complaints of damageto the product. The author’s foal for making this research reportis to implement a customer support and complaint service system for Justmine Beauty products. Based on the result of the application that has been built, researchers can display consultation and complaint services so that users can consult and make mobile-based complaints.